Review of the genus Chirodisca Emeljanov, 1996 (Hemiptera: Fulgoroidea: Caliscelidae) - Gnezdilov, Vladimir M. (Zootaxa, 2024)
The caliscelid genus, Chirodisca Emeljanov, 1996 (Caliscelinae, Caliscelini), is reviewed. Adults and 5th instar nymph of Chirodisca astyages (Dlabola, 1982) and adults of Ch. eximia (Stål, 1859) are described and illustrated on the basis of type specimens and other material examined. Caliscelis macbridei Fernando, 1960 is synonymised with Ch. eximia (Stål, 1859). The composition and distribution of the genus are revised and discussed, and new records from the Palaearctic, Oriental and Afrotropical Realms are given for both species.